2014
DOI: 10.3390/microarrays3040263
|View full text |Cite
|
Sign up to set email alerts
|

Expression Comparison of Oil Biosynthesis Genes in Oil Palm Mesocarp Tissue Using Custom Array

Abstract: Gene expression changes that occur during mesocarp development are a major research focus in oil palm research due to the economic importance of this tissue and the relatively rapid increase in lipid content to very high levels at fruit ripeness. Here, we report the development of a transcriptome-based 105,000-probe oil palm mesocarp microarray. The expression of genes involved in fatty acid (FA) and triacylglycerol (TAG) assembly, along with the tricarboxylic acid cycle (TCA) and glycolysis pathway at 16 Week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…The KARs and ENRs which were involved in the FA biosynthesis pathway were up‐regulated corroborates previous study . The HAD was abundance at 18 WAA then decreased towards ripening (20 WAA) displaying a different trend compared to the upregulation of transcriptome towards oil palm fruit ripening . Previous studies also reported that FA biosynthetic enzymes were upregulated throughout oil palm fruit ripening at transcriptome and proteome levels .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The KARs and ENRs which were involved in the FA biosynthesis pathway were up‐regulated corroborates previous study . The HAD was abundance at 18 WAA then decreased towards ripening (20 WAA) displaying a different trend compared to the upregulation of transcriptome towards oil palm fruit ripening . Previous studies also reported that FA biosynthetic enzymes were upregulated throughout oil palm fruit ripening at transcriptome and proteome levels .…”
Section: Resultssupporting
confidence: 89%
“…Moreover, almost all the key FA biosynthetic machinery indicated the utmost transcription level at 17 WAA where the onset of oil accumulation starts . The highly expressed proteins associated with lipid biosynthesis correspond to an increase in transcriptome and proteome levels throughout mesocarp development . This finding is in parallel with the FAS enzyme activities in lipid biosynthesis which regulates the oil yield and quality in developing fruits .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Our Group previously found differential in gene expression as well as protein and metabolite levels in glycolysis pathway were associated with mesocarp oil content 3 , 4 , 16 . In this study, we validated the oil palm glycolytic gene function through loss-of-function mutants in Saccharomyces cerevisiae as a model system.…”
Section: Introductionmentioning
confidence: 85%
“…All mesocarp samples were characterized using parallel profiling techniques for the transcript (cDNA microarrays), protein/peptide (UPLC-MS, MALDI-TOF/TOF-MS) and metabolite (GC-MS, CE-MS, LC-MS) levels. A custom oil palm transcriptome microarray was developed using the Agilent platform [111] as a tool to study gene expression profiles of mesocarp tissue. Biochemical changes before, during, and after oil biosynthesis in the fruit mesocarp were compared to gain a deeper understanding of the control of oil biosynthesis in the oil palm [104].…”
Section: Oil Palm Omics Research Related To Yieldmentioning
confidence: 99%